THE RIGHT TO BE FORGOTTEN: LEGAL IMPLICATIONS IN THE CONNECTED INFORMATION ERA - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (Jurnal Komunikasi, 2025)
This article discusses the concept of the ‘Right to Be Forgotten’ in the context of an increasingly connected digital era. This right allows individuals to request the removal of their personal data that is irrelevant, outdated, or misleading from online search results, thus giving them greater control over their personal information scattered on the internet. However, the implementation of this right raises complex legal challenges, particularly in balancing individual privacy rights with freedom of public information. This article explores the existing legal framework, as well as the social and ethical implications of implementing the ‘Right to Be Forgotten’. Thus, this article underlines the need for a flexible and balanced policy framework to accommodate technological developments without compromising the principles of transparency and access to information